President Benigno C. Aquino’s Inaugural Address: A Critical Discourse Analysis - Romel R. Costales (Randwick International of Education and Linguistics Science Journal, 2021)
This paper looked into the persuasive strategies of President Benigno Simeon “Noynoy” Aquino III’s public speaking and the hidden ideology that was present in his inaugural speech. Norman Fairclough’s (1995) assumptions in critical discourse analysis that ideologies can be found in texts, that such ideologies can be impossibly separated from texts and that “texts are open to diverse interpretations” was the basis of the study. President Aquino’s persuasive strategies were shown through the evaluation of the ideological and persuasive components of his inaugural speech.